Pemberdayaan Kelompok Peternak Sapi di Desa Poto: Langkah Menuju Kemandirian Berkelanjutan - Salam, Abdul; Hartini, Hartini; Husni, Husni (Abdimas Indonesian Journal, 2024)
Sumbawa cattle have been marketed for local, regional and national market needs, especially during the Eid al-Adha and markets in big cities throughout Indonesia. The high market demand is not balanced with an increase in the quality of Sumbawa cattle, so it has not fully answered market needs, the solution for its independence in managing livestock, market networks, distribution and mechanisms to enter industry needs and feed processing skills, abundant feed sources in the rainy season, and inversely proportional to the supply of feed in the dry season, this has an impact on the productivity of cattle farmers which is very lacking. unable to improve the welfare and independence of cattle breeders and the community in general. Sumbawa cattle are an important livestock commodity and have high and strategic economic value. After training and mentoring, it can increase the independence and productivity of farmers up to 1.5 to 2 times, due to the availability of feed banks, livestock nutrition and vitamins.